Determination and Prioritizing of the Factors Affecting the Tolerance to Shift Work Using Techniques of the Delphi and Fuzzy Analytical Hierarchical Process - Mahnaz Shakerian; Saeid Yazdanirad; Amir Hossein Khoshakhlagh; Seyed Mahdi Mousavi (International Journal of Environmental Health Engineering)
Aim: This study aimed to identify, classify, and prioritize the factors affecting tolerance to shift work using Delphi and fuzzy analytical hierarchy process (FAHP) techniques. Methods: This descriptive analytical study was conducted in 2023. First, the literature review and Delphi technique identified the factors affecting tolerance to shift work. Then, these factors were grouped into five categories. The FAHP was used to prioritize the factors. Finally, the data were analyzed using MATLAB software (version 2019a). Results: Thirty-two factors were identified and grouped into five categories. Based on the results of FAHP, the relative weights of individual factors, working conditions, working hours, family and living conditions, and social conditions were computed as 0.231, 0.211, 0.187, 0.186, and 0.182, respectively. Conclusion: These results highlight the significance of factors influencing tolerance to shift work and can aid in planning preventive measures for the decrease of shiftwork disorders.